The Influence Of Intellectual Capital And Institutional Ownership On Financial Performance With Corporate Social Responsibility As A Moderation Variable - Misdar Misdar (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to determine and analyze the influence of intellectual capital and institutional ownership on financial performance withsocial responsibility as moderation. Population a inthis study is bank subsector companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling method used is purposive sampling. The information used in this study was obtained from financial information published on www.idx.co.id website.